The Determinants of Rural Bank Profitability are Moderated by Credit Risk and Bank Size - Kencana Dewi, Ida Ayu Komang Alit; Suaryana, I Gusti Ngurah Agung (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the effect of capital adequacy and credit distribution on profitability, with credit risk and bank size as moderating variables, at Rural Banks in Bali during the 2020–2024 period. This study uses a quantitative approach, with the population consisting of all BPRs in Bali registered with the Financial Services Authority. The sample was determined using purposive sampling, resulting in 128 BPRs as the study sample over a five-year observation period, producing a total of 640 observations. Data were obtained through documentation techniques from the annual financial statements of the BPRs and analyzed using Moderated Regression Analysis (MRA) with the help of SPSS. The results indicate that capital adequacy, proxied by the Capital Adequacy Ratio (CAR), has a positive effect on profitability, proxied by Return on Assets (ROA). Meanwhile, credit distribution, proxied by the Loan to Deposit Ratio (LDR), has no significant effect on profitability. Credit risk, proxied by Non-Performing Loans (NPL), was found to weaken the positive effect of capital adequacy on profitability but did not moderate the relationship between credit distribution and profitability. Additionally, bank size was not proven to moderate the relationships between either capital adequacy or credit distribution and BPR profitability in Bali during the study period. These findings highlight the importance of managing capital alongside credit risk control to enhance the financial performance of BPRs.